The Role of Social Media Customer Engagement on Satisfaction and Loyalty to Universities - Praditya, Rayyan (Journal of Industrial Engineering & Management Research, 2019)
This study aims to analyze the effect of social media customer engagement and student satisfaction on college loyalty as a brand, as well as the role of student and alumni satisfaction as a mediator. The study used a survey method which was conducted on 180 students of a private university in Tangerang who were selected by simple random sampling method. Data analysis using structural equation modeling (SEM) with data processing tools for the SmartPLS 3.0 program revealed the results of research that social media customer engagement has a significant influence in increasing loyalty to universities. Student and alumni satisfaction has a significant effect on increasing loyalty to universities, as well as a mediator that significantly influences social media customer engagement on student and alumni loyalty to universities.